2018
DOI: 10.1177/0363546518770436
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stimulation Technique Augmented by an Ultrapurified Alginate Gel Enhances Cartilage Repair in a Canine Model

Abstract: The data support the clinical reality of 1-step minimally invasive cartilage-reparative medicine with UPAL gel without harvesting donor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…Although it is difficult to compare the results of our study with this one because of different factors, the stiffness of regenerated tissue in the UPAL gel group was almost identical to that in our 2 previous studies. 6,7 Nonetheless, we and the authors of the other study agree that longer duration may improve the stiffness of regenerated tissue.…”
Section: Discussionsupporting
confidence: 57%
“…Although it is difficult to compare the results of our study with this one because of different factors, the stiffness of regenerated tissue in the UPAL gel group was almost identical to that in our 2 previous studies. 6,7 Nonetheless, we and the authors of the other study agree that longer duration may improve the stiffness of regenerated tissue.…”
Section: Discussionsupporting
confidence: 57%
“…As far as results were concerned, Quiang et al [43] and Baba et al [45] found similar trends between histological and biomechanical analyses; both works measured the cartilage stiffness by means of the indentation test, whereas in the work of Quiang, histomorphometry was conducted by measuring the 3D bone volume by microCT, and in the work of Baba, semiquantitative Niederauer and Changoor scores were adopted.…”
Section: Resultsmentioning
confidence: 93%
“…[10][11][12] Low durability of the repaired cartilage is attributed to the new cartilage being fibrocartilage-like, which has inferior mechanical properties to articular hyaline cartilage. 13,14 Gels, such as alginate, have also been used have been used in modified AMIC trials in animal studies, 15 however, hydro-gels provide limited initial support due to inferior mechanical properties and further modifications, e.g. incorporation of matrix derived molecules such as collagen Type I or II, are often required for endogenous stem cell recruitment.…”
Section: Introductionmentioning
confidence: 99%